Molecular Characterisation of Virulence and Antibiotic Resistance Genes in Diarrhoeal Shigella Isolates from Diwaniyah, Iraq - Zahraa Rijah; Ahlam Al-Galebi (Babcock University Medical Journal)
Objective: Investigating the genetic diversity, virulence determinants, and resistance profiles of Shigella spp is essential to managing outbreaks and informing effective treatment measures, especially in the Iraqi setting, where such data is scarce.